2016
DOI: 10.1007/s11069-016-2168-5
|View full text |Cite
|
Sign up to set email alerts
|

The fire extinguishing performances of foamed gel in coal mine

Abstract: Experiments have been made to investigate how mass concentrations of thickener and crosslinker blends and foaming multiple affect temperature resistance of foamed gel. The results show that, at 100°C, the time for temperature tolerance of common foam is only 196 s, while the time of foamed gel formed by thickener and crosslinker with the mass fractions of both 0.3, 0.4 and 0.5 % is 570, 604 and 780 s, respectively. When the foaming multiple is 5, the time for temperature resistance is 620 s. But the time reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…In general, the oxidative exothermic of coal in low temperature stage is the direct cause of spontaneous combustion of coal[2426]. In previous studies, the control of spontaneous combustion in mine goaf includes two parts: inhibit low temperature oxidation of coal[2729] and extinguish high temperature combustion of coal[30–33]. Thus, the experiment of inhibiting low temperature oxidation of coal by NIWM and extinguishing high temperature combustion of coal by NIWM were carried out, respectively.…”
Section: Experimental Research On Niwm Fire Prevention and Extinguishingmentioning
confidence: 99%
“…In general, the oxidative exothermic of coal in low temperature stage is the direct cause of spontaneous combustion of coal[2426]. In previous studies, the control of spontaneous combustion in mine goaf includes two parts: inhibit low temperature oxidation of coal[2729] and extinguish high temperature combustion of coal[30–33]. Thus, the experiment of inhibiting low temperature oxidation of coal by NIWM and extinguishing high temperature combustion of coal by NIWM were carried out, respectively.…”
Section: Experimental Research On Niwm Fire Prevention and Extinguishingmentioning
confidence: 99%
“…Subsequently, at this concentration, the effects of the foaming ratio, addition of salts (NaCl, CaCl 2 and AlCl 3 ), pH value and temperature on the rheological properties of the foam gel were discussed [60]. The fire extinguishing time of thickening agent and crosslinking agent mixture at different concentrations was also examined [61].…”
Section: Polymer-containing Soft Matters For Coal Mine Disaster/hamentioning
confidence: 99%
“…Fire extinguishing experiments revealed that the intelligent gel could cover the surface of burning coal, thereby significantly reducing the ignition source temperature, thermal radiation, and amount of CO generated. Zhang et al 14 prepared a gel made up of thickener, cross-linker, foaming agent, water, and nitrogen.…”
Section: Introductionmentioning
confidence: 99%